A Study on the Calculation, Design, and Fabrication of a Radio Frequency Drying System - Lieu Le Quang; Liviu Giurgiulescu; Hung Do Xuan; Dzung Nguyen Tan (Journal of Technical Education Science, 2026)
This study presents the results of the calculation, design, and fabrication of a high-frequency electric field (radio frequency, RF) drying system with a capacity of 1000 kg per batch and a drying time of 1.2 hours per batch. Based on material and energy balance analyses, the principal technical parameters of the system were determined, providing the foundation for mechanical design, installation of the RF power supply, and development of the automatic control system. After completion, the system was experimentally operated to evaluate its operational stability and performance efficiency through the drying of seasoned anchovies, in comparison with a conventional hot-air convective drying method. The experimental results show that the system operated stably throughout the entire drying process, with a rapid moisture reduction rate and a drying time reduced by approximately 90% compared with conventional convective drying. The specific energy consumption was 10–12% lower, while the sensory quality of the product was higher (9.4 compared with 8.6) across the entire investigated moisture range, with an optimal moisture content of approximately 8–9%. These findings confirm the high feasibility of the radio frequency (RF) drying system, demonstrating that it meets technological requirements and has strong potential for application in industrial-scale production.